2015
DOI: 10.5194/acp-15-8987-2015
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and solubility of trace elements in fine particles at a mountain site, southern China: regional sources and cloud processing

Abstract: Abstract. The concentrations and solubility of twelve trace elements in PM2.5 at Mt. Lushan, southern China, were investigated during the summer of 2011 and the spring of 2012. The average PM2.5 mass was 55.2 ± 20.1 μg m−3 during the observation period. Temporal variations of all trace elements including total and water-soluble fractions with several dust storm spikes in total fractions of Al and Fe were observed. The enrichment factor (EF) values were 1 order of magnitude higher for the water-soluble fraction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 63 publications
5
37
0
Order By: Relevance
“…Most elements had similar solubility in coarse and fine aerosols during nondust periods, while As, Pb, and Ba appeared to be more soluble in fine mode than coarse mode, with a solubility discrepancy of ~10%. In addition, trace elements in fine aerosols at Mount Heng showed approximately comparable solubility with those at Mount Lushan [ Li et al ., ], except for more soluble Se and Cd and less soluble Cu and Fe. However, the declined solubility of trace elements in both coarse and fine aerosols during dust periods was clearly observed, indicating the suppressed dissolution of aerosol elements by dust storms, which was largely attributable to the decreased aerosol acidity (see Text S3) from abundant alkaline substances.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most elements had similar solubility in coarse and fine aerosols during nondust periods, while As, Pb, and Ba appeared to be more soluble in fine mode than coarse mode, with a solubility discrepancy of ~10%. In addition, trace elements in fine aerosols at Mount Heng showed approximately comparable solubility with those at Mount Lushan [ Li et al ., ], except for more soluble Se and Cd and less soluble Cu and Fe. However, the declined solubility of trace elements in both coarse and fine aerosols during dust periods was clearly observed, indicating the suppressed dissolution of aerosol elements by dust storms, which was largely attributable to the decreased aerosol acidity (see Text S3) from abundant alkaline substances.…”
Section: Resultsmentioning
confidence: 99%
“…Fe was the most predominant trace element in both fine and coarse aerosols at Mount Heng during nondust periods, followed by Al and Zn, but their concentrations were obviously lower than those at Mount Tai in the North China Plain [ Deng et al ., ]. High concentrations of toxic Pb (108.6 ng m −3 ), As (21.1 ng m −3 ), and Cd (5.55 ng m −3 ) in fine aerosols were observed at Mount Heng, which were likely contributed by the heavy metal pollution in the Chang‐Zhu‐Tan city clusters and were comparable to the levels at Mount Lushan [ Li et al ., ]. However, overall, most trace elements at Mount Heng had lower concentrations than those at Mount Dinghu in the Pearl Delta Region [ Yang et al ., ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some TEs can serve as important catalysts in sulfate formation and thus further result in degradation of the air quality (Harris et al, ; He et al, ). Some transition metal ions can also affect the HO x budgets and thereby influence the oxidation capacity of the atmosphere (Fomba et al, ; Li et al, ). Although several studies have found that the formation of sulfate was associated with TEs (Clements et al, ; Gankanda et al, ; Harris et al, ; He et al, ; Huang et al, ; Xie et al, ), the statistical relationship between TEs and sulfate formation has not been systemically investigated due to inadequate in situ observation data.…”
Section: Introductionmentioning
confidence: 99%
“…One-eighth of the sample filter and the blank filter were cut into fragment and digested at 151 170 ℃ for 4 h in a high pressure Teflon digestion vessel with 3 mL of HNO3 and 1 mL of 152 HClO4 (Wang et al, 2006;Li et al, 2015b). After cooling, the digested solution was filtered and 153 diluted to 15 mL with less than 2% acidity with ultrapure Mill-Q water.…”
Section: Introduction 22mentioning
confidence: 99%